The Consumption Space Paradox: Over‑Retailed Areas Next to Dead Malls - Bednarowska, Zofia (Acta Universitatis Lodziensis. Folia Oeconomica, 2018)
We are witnessing a paradox in the consumption space, in relation to retail activity within urban and suburban areas: One can observe over‑retailed areas, featuring retail chains and shopping malls, oftentimes occurring close to other unoccupied, abandoned, dying shopping malls, called dead malls. The phenomenon of dead malls is widespread in the USA, is strongly visible in Canada and China, and is now starting to occur more often in Europe. This paradox can be partially explained using a series of concepts, and in this paper we introduce the main pillars in understanding the socio‑economic reasons and the spatial patterns contributing to this phenomenon. The research method employed here is the ESDA (Exploratory Spatial Data Analysis).